Konsep Manajemen Pendidikan Islam Perspektif Al-Qur’an - Suriani, Irda; Harahap, Tiara Febriani; Siregar, Hilda Hilda Darmaini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Educational management is management that is applied in the development of education. In the sense that it is the art and science of managing Islamic educational resources to achieve the goals of Islamic education effectively and efficiently. This research aims to find out the concept of Islamic education management based on the perspective of the Qur'an and Hadith. This study uses a literature review method to examine the concept of Islamic education management from the perspective of the Qur'an. This research involves the systematic collection and analysis of relevant sources, including classical and contemporary interpretations (Qur'anic interpretations), scientific articles, books, and other academic works related to Islamic education management and Qur'an principles. The data are categorized and interpreted to identify the core principles and practices in education management as outlined in the Qur'an. The results of the analysis show that the purpose of Islamic education management is so that all resources, equipment or facilities in an organization can be mobilized in such a way that it can avoid to the minimum extent all the waste of time, energy, materials, and money in order to achieve the organizational goals that have been set in advance. The views of experts conclude that the concept of Islamic education management according to the perspective of the Qur'an is as follows, namely flexible, effective, efficient, open, cooperative and participatory